2018
DOI: 10.3390/f9020087
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Biosynthesis of Anthocyanins in Begonia semperflorens under Low-Temperature and High-Light Conditions

Abstract: Abstract:Anthocyanins are considered a stress indicator due to their involvement in the response to many stresses including high light (HL) and low temperature (LT). With the development of transcriptomics, it is necessary to find the different and common points in the mechanisms of LT-induced and HL-induced anthocyanin biosynthesis. In the present study, we determined the transcriptomes of Begonia semperflorens leaves under three different conditions (normal growing conditions (CK), HL, and LT). To validate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Generally, the structural genes, like CHI, CHS, DFR, and ANS, within the flavonoid metabolic pathway significantly influence the flavonoid content [35,36]. High light is known to induce anthocyanin biosynthesis by up-regulating these structural genes, such as PAL, CHS, F3H, and ANS genes [18]. And our study reveals a novel aspect, where F3 ′ H gene expression was markedly up-regulated with increased light intensity (Table S6 and Figure 7).…”
Section: Anthocyanin Was Induced By Light Conditionsmentioning
confidence: 62%
See 3 more Smart Citations
“…Generally, the structural genes, like CHI, CHS, DFR, and ANS, within the flavonoid metabolic pathway significantly influence the flavonoid content [35,36]. High light is known to induce anthocyanin biosynthesis by up-regulating these structural genes, such as PAL, CHS, F3H, and ANS genes [18]. And our study reveals a novel aspect, where F3 ′ H gene expression was markedly up-regulated with increased light intensity (Table S6 and Figure 7).…”
Section: Anthocyanin Was Induced By Light Conditionsmentioning
confidence: 62%
“…All of the unigenes were aligned to the NR, Swiss-Prot, Horticulturae 2024, 10, 96 5 of 14 KEGG, KOG, eggNOG, GO, and Pfam protein databases. And the results showed that 31,197,24,591,12,096,18,309,30,226,22,489, and 41 unigenes were identified in the NR, Swiss-Prot, KEGG, KOG, eggNOG, GO, and Pfam protein databases, respectively (Table 3). Most unigenes were annotated in NR protein databases, reaching 72.49%.…”
Section: Transcriptome Functional Annotationmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature will affect stability of the betacyanins of Monascus ( Abdollahi et al., 2021 ). Low temperature can induce accumulation of anthocyanins in begonia, which has a protective effect against low temperature stress ( Dong et al., 2018 ). Betacyanins have similar functions to anthocyanins, making plants brightly colored.…”
Section: Discussionmentioning
confidence: 99%